A rare case of reactive arthritis with intermittent hematuria in a young male - Pallivalappil, Bhargavan; Jacob, Anuja; Khan, Sadab Raza; Khader, Sherin; Mekkayil, Babitha (International Journal of Advances in Medicine, 2023)
Reactive arthritis (ReA) is an inflammatory arthritis that manifests days to weeks after a gastrointestinal or genitourinary infection. It is also described as a classic triad of arthritis, urethritis, and conjunctivitis. Here we discuss the clinical presentation of ReA in a 20-year-old male who presented with typical triad of symptoms. But there was presence of hematuria which couldn’t be explained by this single diagnosis. So further investigations where necessary to find the cause of his haematuria. A 20-year-old male student with history of childhood onset renal stone disease presented with complaints of dysuria for 3 days followed by bilateral conjunctival congestion along with pain around right hip joint, painful swelling around right ankle joint for 2 days. All examination were normal except for bilateral conjunctivitis and features of right ankle joint arthritis. His blood investigations showed neutrophilic leucocytosis with raised CRP levels. Chlamydia IgM Antibody was detected positive, which revealed the causative organism being Chlamydia Trachomatis. Urine routine showed 50-55 RBC’S and 2+ proteinuria. Hematuria was attributed to the CT evidence of renal stone and abnormal retroaortic coarse of his left renal vein described as posterior nutcracker syndrome.